2013
DOI: 10.7314/apjcp.2013.14.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Screening of MicroRNA in Patients with Esophageal Cancer at Same Tumor Node Metastasis Stage with Different Prognoses

Abstract: Patients at the same pathological stage of esophageal cancer (EC) that received the same surgical therapy by the same surgeon may have distinct prognoses. The current study aimed to explore the possibility of differentiallyexpressed microRNAs (miRNAs) underlying this phenomenon. Samples were collected from EC patients at the same tumor node metastasis (TNM) stage but with different prognoses. Paracancerous normal tissues were taken as controls. The specimens were histopathologically analyzed. Differentially-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…35 This result is reasonable since it has been frequently demonstrated that miRNA may have oncogenic or tumor suppressor activity depending on the cell context. 36 In our previous works we have identified other miRNAs that are downregulated in gonadotroph adenomas starting from the analysis of GH-secreting adenomas.…”
Section: Wwwtandfonlinecommentioning
confidence: 85%
“…35 This result is reasonable since it has been frequently demonstrated that miRNA may have oncogenic or tumor suppressor activity depending on the cell context. 36 In our previous works we have identified other miRNAs that are downregulated in gonadotroph adenomas starting from the analysis of GH-secreting adenomas.…”
Section: Wwwtandfonlinecommentioning
confidence: 85%
“…They participate in a number of pathological and physiological processes and become a promising therapy target with clinical value (Calin et al, 2005;Castilla et al, 2011). MiR-29a was up-regulated in esophageal Cancer with well prognosis (Zhao et al, 2013) , it may affect the prognosis of the tumor, but it was lack of in-depth research, In bile duct carcinoma cell lines, human hepatocellular carcinoma cell lines and acute myeloid leukemia cell lines, miR-29 could regulate apoptosis by targeting MCL-1. Over-expression of miR-29 could down-regulate the expression of MCL-1 (Mott et al, 2007;Xiong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since traditional methods could not provide an accurate prediction for the prognosis of advanced ESCC patients, it is very necessary and worthy to develop a more sensitive and specific biomarker. Recently, researches of genetic biomarkers have identified a lot of ESCC prognositic factors, such as CYFRA21-1, CEA, hemoglobin and microRNAs (Zhang et al, 2013;Zhao et al, 2013). However, improvement of existing prognosis system and discovery of new prognositic factors are still important and full of clinical significance.…”
Section: Introductionmentioning
confidence: 99%